Split or full-body workout routine: which is best to increase muscle strength and hypertrophy? - Evangelista,Alexandre Lopes (2021)
ABSTRACT Objective: To compare the effects of different resistance training programs on measures of muscle strength and hypertrophy. Methods: Sixty-seven untrained subjects were randomized to one of two groups: Split Workout Routine (n=35), in which muscle groups were trained twice per week in an A/B split consisting of eight sets per session, or Full-Body Workout Routine (n=32), in which muscle groups were trained four times per week with four and eight sets per session. Both groups performed eight to 12 repetition maximum per set, with 60 seconds of rest between sets. Maximal strength and muscle thickness were assessed at baseline and after eight weeks of training. Results: A significant main effect of time (pre versus post) was observed for maximal strength in the bench press and squat exercises and thickness of the elbow extensor, elbow flexor and quadriceps femoris muscles. Selected variables did not differ significantly between groups. Conclusion: Resistance training twice or four times per week has similar effects on neuromuscular adaptation, provided weekly set volume is equal.